Pengaruh Perilaku Pembelian Mahasiswa terhadap Keputusan Pembelian Komputer Notebook di Lingkungan Mahasiswa Bina Nusantara International - Enggal Sriwardiningsih; Lydia Angelia; Lisa Aulia (The Winners, 2006)
Customer decision the goal of the research is to clarify that to buy product is influenced by four factors; those are culture, social, characterictic individu, and psycology. Analysis was done by consumer behavior theory, consumer buying, decision, validity and reliability tests. The result of the research show that these factors influence strongly, expecially individual factor influence very strong.